NEGLECTED CASE OF RUPTURED UTERUS: Case of Ruptured Uterus - Perveen, Dr Saima; Naheed, Farrukh; Sultana, Azra (Pakistan Armed Forces Medical Journal, 2012)
Rupture of the uterus is a grave obstetric complication that is associated with high maternal and perinatal mortality. It may be complete which involve the entire uterine wall or incomplete, when a cover of viseral peritoneum or broad ligament is left over the uterus. It often involves scarred uterus, secondary to previous caesarean delivery1. The rise in cesarean section rate has increased the number of women exposed to the risk of complication. However unrelieved obstructed labour due to macrosomic or abnormal fetus remains the major cause of uterine rupture, usually occurring in grand multiparous patients2. A maternal and fetal outcome usually with an unscarred uterus is worse than in those with a previous uterine scar3.